Pentingnya Penggunaan Bahasa Indonesia Yang Benar Dalam Interaksi Sehari-Hari Anak Usia Dini - Pulungan, Nailah; Aprilia, Dinda; A, Amelianda; Agustina, Ade; Putri, Anggia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Early childhood language development is language development that children must have as one of the basic abilities, according to their age stages and developmental characteristics. This research generally aims to improve oral language, specifically finding out how much oral language ability is through the application/use of storytelling methods. This research was carried out in class B of harapan islamiah.. The research subjects were 22 students consisting of 6 boys and 16 girls. The data for this research are data on students' oral language skills, data collection instruments using observation sheets and data collection techniques through observation. The data analysis technique uses a comparative descriptive method, namely comparing cycle I and cycle II each in two meetings. Based on the analysis of the data obtained, learning activities used II cycles, totaling 4 meetings. In cycle I, the number of presentations was 36.4%, followed by meeting II at 54.5%. Meanwhile, in cycle II, meeting I, it was 68%, followed by meeting II to 86.4%. This increase has exceeded learning completion. The results of the research show that the storytelling method which is done repeatedly can train children's concentration in improving language skills through listening and expressing language in group B of harapan islamiah